Limitation of C4 photosynthesis by low carbonic anhydrase activity increases with temperature but does not influence mesophyll CO2 conductance. (26th October 2021) - Crawford, Joseph D; Cousins, Asaph B
Abstract: The CO2 -concentrating mechanism (CCM) in C4 plants is initiated by the uptake of bicarbonate (HCO3 − ) via phospho enol pyruvate carboxylase (PEPC). Generation of HCO3 − for PEPC is determined by the interaction between mesophyll CO2 conductance and the hydration of CO2 to HCO3 − by carbonic anhydrase (CA). Genetic reduction of CA was previously shown not to limit C4 photosynthesis under ambient atmospheric partial pressures of CO2 ( p CO2 ). However, CA activity varies widely across C4 species and it is unknown if there are specific environmental conditions (e.g. high temperature) where CA may limit HCO3 − production for C4 photosynthesis. Additionally, CA activity has been suggested to influence mesophyll conductance, but this has not been experimentally tested. We hypothesize that CA activity can limit PEPC at high temperatures, particularly at low p CO2, but does not directly influence g m . Here we tested the influence of genetically reduced CA activity on photosynthesis and g m in the C4 plant Zea mays under a range of p CO2 and temperatures. Reduced CA activity limited HCO3 − production for C4 photosynthesis at low p CO2 as temperatures increased, but did not influence mesophyll conductance. Therefore, high leaf CA activity may enhance C4 photosynthesis under high temperature when stomatal conductance restricts the availability of atmospheric CO2 . Abstract : Carbonic anhydrase activity enhances the ease with which C4 plants acquire CO2 and may be beneficial in drought conditions to optimize CO2 assimilation when water is limiting.